2003
DOI: 10.1525/sop.2003.46.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Friendships as Academic Resources: The Intersection of Friendship, Race, and School Disadvantage

Abstract: Research on adolescent friendships has typically treated these social ties differently from friendships at other stages of life or from other relationships during adolescence. To draw parallels among these literatures, this study focuses on two largely neglected aspects of adolescent friendships: their role in positive adjustment and the way in which this role varies by social structural and institutional context. In an analysis of data from 9,223 adolescents in the National Longitudinal Study of Adolescent He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
189
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(197 citation statements)
references
References 32 publications
6
189
0
2
Order By: Relevance
“…It is thus no surprise that research has found friends to shape adolescents' educational outcomes both positively and negatively by directly influencing their friends' grades (Ryan 2001;Flashman 2012a;Rambaran et al 2016), by protecting each other from academic failure (Crosnoe et al 2003), and motivating more advanced course taking (Riegle-Crumb et al 2006). Because of these social influence processes, friends tend to become more similar over time in terms of their motivation and achievement in school.…”
Section: Social Influence and Selection In Academic Achievementmentioning
confidence: 99%
“…It is thus no surprise that research has found friends to shape adolescents' educational outcomes both positively and negatively by directly influencing their friends' grades (Ryan 2001;Flashman 2012a;Rambaran et al 2016), by protecting each other from academic failure (Crosnoe et al 2003), and motivating more advanced course taking (Riegle-Crumb et al 2006). Because of these social influence processes, friends tend to become more similar over time in terms of their motivation and achievement in school.…”
Section: Social Influence and Selection In Academic Achievementmentioning
confidence: 99%
“…In fact, cross-ethnic friendships improve perspective taking (Eisenberg et al, 2009), resilience (Bagci, Rutland, Kumsahiro, Smith, & Blumberg, 2014), and social skills (Lease & Blake, 2005) and therefore equip children with necessary skills to moderate prejudicial attitudes (Fitzroy & Rutland, 2010). Second, this kind of information exchange across ethnic boundaries also provides children with a varied range of reference points to evaluate themselves (Antonio, 2004), and functions like 'social capital', providing children with opportunities to access important information about being successful in an ethnically diverse society (Crosnoe, Cavanagh, & Elder, 2003).…”
mentioning
confidence: 99%
“…Les jeunes en difficulté et en décro-chage se tournent notamment vers leurs pairs pour fuir leur mal-être à l'école et dans la famille et restaurer leur image de soi dévalorisée. Malheureusement, il s'agit le plus souvent de pairs dont la fréquentation fait augmenter les risques de décrochage scolaire (Crosnoe et al 2003 ;Thin et Millet 2005). Un des jeunes décrocheurs souligne que la participation à des activités extrascolaires intéressantes et la diversification des groupes d'amis auraient pu avoir un impact positif sur sa trajectoire, tel que le montrent certaines études (Glanville et al 2008).…”
Section: L'influence Des Pairsunclassified